2019
DOI: 10.1097/mpa.0000000000001430
|View full text |Cite
|
Sign up to set email alerts
|

Rising Prevalence of Opioid Use Disorder and Predictors for Opioid Use Disorder Among Hospitalized Patients With Chronic Pancreatitis

Abstract: Objectives We aimed to evaluate the prevalence, impact, and predictors of opioid use disorder (OUD) in hospitalized chronic pancreatitis (CP) patients. Methods A retrospective cohort study was performed using the National Inpatient Sample database from 2005 to 2014. Patients with a primary diagnosis of CP and OUD were included. The primary outcome was evaluating the prevalence and trend of OUD in patients hospitalized with CP. Secondary outcomes were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
16
0
3
Order By: Relevance
“…Chronic pancreatitis: In one RCT comparing morphine and fentanyl, both medications did not significantly reduce pain and disability (Niemann et al, 2000). In US cohort studies, opioid use was associated with opioid use disorder (Bilal et al, 2019). According to the clinical experience, up to 25% of patients can experience pain relief associated with opioid use (Drewes et al, 2017).…”
Section: Controversial Issuesmentioning
confidence: 99%
“…Chronic pancreatitis: In one RCT comparing morphine and fentanyl, both medications did not significantly reduce pain and disability (Niemann et al, 2000). In US cohort studies, opioid use was associated with opioid use disorder (Bilal et al, 2019). According to the clinical experience, up to 25% of patients can experience pain relief associated with opioid use (Drewes et al, 2017).…”
Section: Controversial Issuesmentioning
confidence: 99%
“…Depression alone has been linked to the risk of opioid relapse [34], opioid misuse [49], a diagnosis of OUD [50], and risk of death from OUD-related overdose [51], while anxiety disorders have been linked to opioid relapse [34], non-medical use [52], and misuse [53]. Figure 2 (orange bars) illustrates how often a psychiatric disease was found to be a significant indicator of a POU phenotype within our literature search criteria (see Review Methods) [10,17,44,47,49,50,. Depression, nicotine use/smoking status, alcohol use, and anxiety disorders were the most common predictors of POU (Fig.…”
Section: Risk Factors Of Poumentioning
confidence: 99%
“…2; orange bars). In addition to these comorbidities as risk factors of POU, the strongest indicators of future POU development are past instances of opioid use or POU [10,17,44,47,49,50,. Due to the nature of the relationship between psychiatric disease and POU, histories of substance use/abuse and mental illness, although sometimes challenging to obtain, are important sources of data for POU risk assessment.…”
Section: Risk Factors Of Poumentioning
confidence: 99%
“…Although potentially effective in pain management, opioid use has serious consequences including narcotic bowel syndrome and opioid-induced hyperalgesia[ 23 ]. It has been shown that about 13%-50% patients with inflammatory bowel disease and irritable bowel syndrome use chronic opioids, and similarly, up to 66% patients of CP are known to use opioids[ 24 - 27 ]. Over the last two decades, opioid use among several gastrointestinal conditions with chronic pain has steadily continued to increase with an 88% increase in inflammatory bowel disease and a 57.6% increase in CP[ 27 ].…”
Section: Pain Management Strategiesmentioning
confidence: 99%